Brain tumor classification of virtual NMR voxels based on realistic blood vessel‐induced spin dephasing using support vector machines. (14th April 2020) - Hahn, Artur; Bode, Julia; Schuhegger, Sarah; Krüwel, Thomas; Sturm, Volker J.F.; Zhang, Ke; Jende, Johann M.E.; Tews, Björn; Heiland, Sabine; Bendszus, Martin; Breckwoldt, Michael O.; Ziener, Christian H.; et al.
Abstract : Remodeling of tissue microvasculature commonly promotes neoplastic growth; however, there is no imaging modality in oncology yet that noninvasively quantifies microvascular changes in clinical routine. Although blood capillaries cannot be resolved in typical magnetic resonance imaging (MRI) measurements, their geometry and distribution influence the integral nuclear magnetic resonance (NMR) signal from each macroscopic MRI voxel. We have numerically simulated the expected transverse relaxation in NMR voxels with different dimensions based on the realistic microvasculature in healthy and tumor‐bearing mouse brains (U87 and GL261 glioblastoma). The 3D capillary structure in entire, undissected brains was acquired using light sheet fluorescence microscopy to produce large datasets of the highly resolved cerebrovasculature. Using this data, we trained support vector machines to classify virtual NMR voxels with different dimensions based on the simulated spin dephasing accountable to field inhomogeneities caused by the underlying vasculature. In prediction tests with previously blinded virtual voxels from healthy brain tissue and GL261 tumors, stable classification accuracies above 95% were reached. Our results indicate that high classification accuracies can be stably attained with achievable training set sizes and that larger MRI voxels facilitated increasingly successful classifications, even with small training datasets. We were able to prove that, theoretically, the transverse relaxation process can be harnessed to learn endogenous contrasts for single voxel tissue type classifications on tailored MRI acquisitions. If translatable to experimental MRI, this may augment diagnostic imaging in oncology with automated voxel‐by‐voxel signal interpretation to detect vascular pathologies. Abstract : We tested the theoretical feasibility of a voxel‐wise classification of MRI acquisitions to detect tumor tissue based on microvascular remodeling effects in such intricately vascularized tissues as the brain. Utilizing support vector machines, the expected transverse relaxation from virtual NMR voxels with known microvasculature (acquired with light sheet fluorescence microscopy) was used to identify previously blinded virtual NMR voxels from tumors and healthy brain tissue with accuracies of up to 90%. Our numerical considerations provided a positive proof‐of‐concept, which can be built upon in experimental analogies, for which the optimal settings can be determined a priori using the toolset developed in this study.